Normative Reconstruction and the Hermeneutics of Recognition - Neculau, Radu (Universidade Estadual de Campinas, 2017)
Axel Honneth’s method of normative reconstruction works by verifying the motivational power of our orienting values, confirming the expressive capacity of practical norms with respect to these values, and sanctioning the adequacy of social institutions to their guiding norms. This paper examines these functions against the conceptual background provided by the notion of recognition as an interpretive practice and in contrast to two theoretical alternatives: Charles Taylor’s account of practical reasoning as reasoning in transitions and Paul Ricoeur’s conception of ideology critique.